PENGARUH PEMAHAMAN BISNIS KLIEN, PENGALAMAN AUDIT DAN KOMPETENSI AUDITOR PADA STRATEGI PENDETEKSIAN KECURANGAN - Lianitami, Putu Wina; Suprasto H, Bambang (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
This study aims to determine the effect of understanding the client's business, audit experience and competence of auditors in fraud detection strategies. This study was performed on a public accounting firm in Bali and East Java are registered in the Certified in 2015. Sampling of this research is the method of non-probability sampling with purposive sampling technique. Data collection methods used in this study was a questionnaire using 5-point Likert scale to measure 52 indicators .. Data analysis technique used is multiple linear regression analysis. Based on the results of the analysis of the research found that the understanding of the client's business strategy has positive effect on fraud detection, auditing experience a positive effect on fraud detection strategy, the competence of auditors positive effect on fraud detection strategies.
Keywords: understanding the client' s business, audit experience, competence of auditors, fraud detection strategy